Design and calibration of the DC electric-field strength measuring instrument by horizontal vibration. Issue 1 (1st November 2022) - Liu, Fengchun; Tu, Shan; Zhang, Yifeng; Liu, Yuhuan
Abstract: The synthesis electric field is an important indicator to assess electromagnetic environment of DC transmission line, and field mill is often used in practical engineering. In order to solve the problem that the shielding plate in the field mill have unreliable grounding due to rotation and the electric field is distorted by accumulated charge, the structure of static shielding plate and moving induction plate are designed in this paper. On this basis, a complete synthetic electric field measuring device is developed. The instrument is calibrated under laboratory conditions, and the results show that calibration curve has good linear characteristic.